2005
DOI: 10.1007/s00540-005-0306-4
|View full text |Cite
|
Sign up to set email alerts
|

Preadministration of low-dose ketamine reduces tourniquet pain in healthy volunteers

Abstract: We evaluated whether preadministration of low-dose ketamine could attenuate tourniquet pain and arterial pressure increase using high tourniquet pressure in ten healthy awake volunteers. Ketamine, 0.1 mg x kg(-1), or normal saline was given intravenously in a double-blind fashion before tourniquet inflation with a pressure of 400 mmHg at the thigh. Visual analog scale (VAS) scores and systolic blood pressure (SBP) were measured at 5-min intervals. Ketamine significantly reduced VAS scores compared to saline ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…[ 8 ] Takada et al . [ 9 ] found that low-dose ketamine attenuates tourniquet pain and arterial pressure increase during high-pressure tourniquet inflation in healthy volunteers. Lee et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 8 ] Takada et al . [ 9 ] found that low-dose ketamine attenuates tourniquet pain and arterial pressure increase during high-pressure tourniquet inflation in healthy volunteers. Lee et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 17 ] This increase in C fibre activity leads to induction of central sensitisation and activation of NMDA receptors,that is part of the mechanism of central sensitisation. [ 5 6 18 ] Although ketamine is an NMDA receptor antagonist and has been shown to be effective in preventing tourniquet-induced hypertension,[ 3 8 9 ] there is a possibility that this effect could be due to relief in tourniquet-induced pain rather than antagonism of NMDA receptors, as ketamine has potent analgesic properties. Furthermore, ketamine is associated with side effects, such as, delirium, hallucinations, tachycardia, hypertension, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonged tourniquet inflation is associated with a gradual increase in arterial blood pressure. The increase in blood pressure is resistant to analgesics and/ or an increase in the depth of anaesthesia 5,6 . The mechanisms involved in tourniquet pain are not well understood but have been postulated to be conducted by A-delta and C-fibres which are thought to mediate somatic pain 3,[8][9][10] .…”
mentioning
confidence: 99%